The Effect of Microencapsulated PCM Slurry Coolant on the Efficiency of a Shell and Tube Heat Exchanger - Marcin Kruzel; Tadeusz Bohdal; Krzysztof Dutkowski; Mykola Radchenko (Energies, 2022)
This paper describes the results of experimental studies on heat transfer in a shell and tube heat exchanger during the phase changes of the HFE 7000 refrigerant. The studies were performed using a mixture of water and a microencapsulated phase change material as a coolant. HFE 7000 refrigerant condenses on the external surface of the copper tube, while a mixture of water and phase change materials flows through the channels as coolant. Currently, there is a lack of research describing cooling using phase change materials in heat exchangers. There are a number of publications describing the heat exchange in heat exchangers during phase changes under air or water cooling. Therefore, the research hypothesis was adopted that the use of mixed water and microencapsulated material as a heat transfer fluid would increase the heat capacity and contribute to the enhancement of the heat exchange in the heat exchanger. This will enable an increase in the total heat transfer coefficient and the heat efficiency of the exchanger. Experimental studies describe the process of heat transfer intensification in the above conditions by using the phase transformation of the cooling medium melting. The test results were compared with the results of an experiment in which pure water was used as the reference liquid. The research was carried out in a wide range of refrigerant and coolant parameters: ṁr = 0.0014–0.0015 kg·s−1, ṁc = 0.014–0.016 kg·s−1, refrigerant saturation temperature Ts = 55–60 °C, coolant temperature at the inlet Tcin = 20–32 °C, and heat flux density q = 7000–7450 W·m−1. The obtained results confirmed the research hypothesis. There was an average of a 13% increase in the coolant heat transfer coefficient, and the peak increase in αc was over 24%. The average value of the heat transfer coefficient k increased by 5%, and the highest increases in the value of k were noted at Tin = 27 °C and amounted to 9% in relation to the reference liquid.